Β-Adrenergic Receptor-Stimulated Cardiac Myocyte Apoptosis: Role of β1 Integrins. (24th May 2011) - Amin, Parthiv; Singh, Mahipal; Singh, Krishna
Abstract : Increased sympathetic nerve activity to the myocardium is a central feature in patients with heart failure. Accumulation of catecholamines plays an important role in the pathogenesis of heart disease. Acting via β -adrenergic receptors (β -AR), catecholamines (norepinephrine and isoproterenol) increase cardiac myocyte apoptosis in vitro and in vivo . Specifically, β 1 -AR and β 2 -AR coupled to Gα s exert a proapoptotic action, while β 2 -AR coupled to Gi exerts an antiapoptotic action. β 1 integrin signaling protects cardiac myocytes against β -AR-stimulated apoptosis in vitro and in vivo . Interaction of matrix metalloproteinase-2 (MMP-2) with β 1 integrins interferes with the survival signals initiated by β 1 integrins. This paper will discuss background information on β -AR and integrin signaling and summarize the role of β 1 integrins in β -AR-stimulated cardiac myocyte apoptosis.